2019
DOI: 10.1111/iwj.13083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endovenous laser treatment and high ligation in treatment of limb varicosity: A meta‐analysis

Abstract: To assess the efficacy and safety of endovenous laser treatment (EVLT) and high ligation (HL) for limb varicosity using meta‐analysis. Multiple databases including PubMed, Springer, Excerpta Medica Database, Ovid Technologies, and China Journal Full‐text database were searched for relevant studies in English or Chinese, and full‐text articles were used to compare EVLT and HL for limb varicosity. Review Manager 5.0 was used to estimate the effects of the results among eligible articles. Forest plots, sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Compared with EVTA, surgically treated patients develop certain complications such as wound infection and haematoma more often, have more intra-operative blood loss, and require a longer operation time. 195 Sensory disturbances are also less common after EVLA compared with surgery. 196 Patients treated with EVTA have less pain and swelling than patients treated surgically.…”
Section: ) the Technique Is Similarmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with EVTA, surgically treated patients develop certain complications such as wound infection and haematoma more often, have more intra-operative blood loss, and require a longer operation time. 195 Sensory disturbances are also less common after EVLA compared with surgery. 196 Patients treated with EVTA have less pain and swelling than patients treated surgically.…”
Section: ) the Technique Is Similarmentioning
confidence: 99%
“…134 A meta-analysis including 11 RCTs, reported a statistically significantly lower recurrence rate after EVLA than after high ligation (3.1% after EVLA vs. 10% after HLS; OR 0.28 [95% CI 0.16 e 0.49] p < .001). 195 Comparing EVLA with RFA, a meta-analysis demonstrated that both have the same safety, efficacy, post-operative pain score, and recanalisation rates. 204 According to two systematic reviews and meta-analyses, recanalisation was the most common cause of recurrence after EVLA, whereas neovascularisation was more frequent after HLS.…”
Section: ) the Technique Is Similarmentioning
confidence: 99%
“…The traditional surgical treatment is the high ligation of the great saphenous vein and superficial vein stripping, which leads to the greater trauma. In the past 20 years, endovenous laser treatment (EVLT) has been widely used due to its advantages of minimal invasion and safety [1][2]. Its principle is to use high-energy laser to fuse the vein wall and to achieve the purposes of the vein closure and the treatment [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the procedure leaves postoperative scars and there is a risk of hyperpigmentation. Moreover, recurrent varicose veins are known to be a common problem after surgery: The literature demonstrates a recurrence rate of 60% after 5 years of follow-up observation [6] . The recurrence is mostly caused by neovascularization, anatomic peculiarities (e.g.…”
Section: Introductionmentioning
confidence: 99%